Authority Of The Commercial Court In Business Competition Cases Post Law No. 11 Of 2020 On Job Creation - Musataklima, Musataklima (Prophetic Law Review, 2021)
The enactment of Law No. 11 of 2020 on Job Creation has had an impact on existing laws. One of the affected laws is Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. The formulation of the problems that will be discussed in this paper is a). How is the existing condition of the authority of the Commercial Court to appeal the KPPU’s decision after the Job Creation Law? b). what is the prospect of bringing cases before the Commercial Court on monopoly and business competition cases after the Job Creation Law? This research uses normative research with a statutory approach, conceptual approach, and a philosophical approach.  Based on the discussion, it can be concluded that, firstly, the existing authority of the Commercial Court’s continues to expand. Currently it is believed to settle the objection cases to the KPPU’s decision through the Job Creation Law. The Commercial Court can examine the formal pleadings and material facts that form the basis of the KPPU’s decision, so that the Commercial Court is not limited in time to complete it. Second, the prospect of the Commercial Court’s authority in cases of unfair business competition is determined by two factors, namely internal factors in the form of the existing condition of the current authority specifically in the field of economic law issues, and the condition of human resources who have been selected and trained and experienced in resolving economic law cases. External factors including (a) the development of the business economy which is increasingly complex and requires an effective, efficient and neutral settlement agency, and the KPPU theoretically has not been able to guarantee a fair process in the settlement of the business competition case because it includes the authority to investigate, investigate, prosecute and adjudicate.Keywords: Authority; Commercial Court; Prospect; Business Competition LawsKewenangan Pengadilan Niaga dalam Kasus Persaingan Usaha Pasca Undang-Undang Nomor 11 Tahun 2020 tentang Cipta KerjaAbstrakPemberlakuan Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja berdampak pada peraturan perundang-undangan yang ada. Salah satu undang-undang yang terdampak adalah UU No. 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Rumusan masalah yang dibahas dalam makalah ini adalah a). bagaimana kewenangan Pengadilan Niaga saat ini untuk mengajukan banding atas putusan KPPU pasca berlakunya UU Cipta Kerja? b). bagaimana prospek permohonan kasus monopoli dan persaingan usaha ke Pengadilan Niaga setelah berlakunya UU Cipta Kerja? Penelitian normatif ini menggunakan pendekatan perundang-undangan, konseptual, dan filosofis. Berdasarkan pembahasan, penelitian ini menyimpulkan bahwa, pertama, kewenangan yang ada dari Pengadilan Niaga saat ini terus berkembang. Saat ini, adalah diyakini bahwa penyelesaian kasus keberatan atas putusan KPPU dapat dilakukan berdasarkan UU Cipta Kerja. Pengadilan Niaga dapat memeriksa dalil-dalil formil dan fakta materiil yang menjadi dasar putusan KPPU sehingga Pengadilan Niaga tidak dibatasi waktu untuk menyelesaikannya. Kedua, prospek kewenangan Pengadilan Niaga dalam perkara persaingan usaha tidak sehat ditentukan oleh dua faktor, yaitu faktor internal berupa kondisi yang ada dari kewenangan saat ini khususnya di bidang hukum ekonomi dan kondisi sumber daya manusia yang telah dipilih dan dilatih serta berpengalaman dalam menyelesaikan kasus-kasus hukum ekonomi. Di samping itu, terdapat faktor-faktor eksternal antara lain (a) perkembangan ekonomi bisnis yang semakin kompleks dan membutuhkan lembaga penyelesaian yang efektif, efisien, dan netral, serta KPPU secara teoretis belum dapat menjamin proses yang adil dalam penyelesaian kasus persaingan usaha karena meliputi kewenangan untuk menyelidiki, menyidik, menunutut, dan mengadili.Kata Kunci: Kewenangan; Pengadilan Niaga; Prospek; Hukum Persaingan Usaha